Kupffer cell and recruited macrophage heterogeneity orchestrate granuloma maturation and hepatic immunity in visceral leishmaniasis - Gabriela Pessenda; Tiago R. Ferreira; Andrea Paun; Juraj Kabat; Eduardo P. Amaral; Olena Kamenyeva; Pedro Henrique Gazzinelli-Guimaraes; Shehan R. Perera; Sundar Ganesan; Sang Hun Lee; David L. Sacks (Nature Communications)
Abstract In murine models of visceral leishmaniasis (VL), the parasitization of resident Kupffer cells (resKCs) drives early Leishmania infantum growth in the liver, leading to granuloma formation and subsequent parasite control. Using the chronic VL model, we demonstrate that polyclonal resKCs redistributed to form granulomas outside the sinusoids, creating an open sinusoidal niche that was gradually repopulated by monocyte-derived KCs (moKCs) acquiring a tissue specific, homeostatic profile. Early-stage granulomas predominantly consisted of CLEC4F+KCs. In contrast, late-stage granulomas led to remodeling of the sinusoidal network and contained monocyte-derived macrophages (momacs) along with KCs that downregulated CLEC4F, with both populations expressing iNOS and pro-inflammatory chemokines. During late-stage infection, parasites were largely confined to CLEC4F-KCs. Reduced monocyte recruitment and increased resKCs proliferation in infected Ccr2 −/− mice impaired parasite control. These findings show that the ontogenic heterogeneity of granuloma macrophages is closely linked to granuloma maturation and the development of hepatic immunity in VL.